Performance and predictors of recruitment success in National Heart, Lung, and Blood Institute's cardiovascular clinical trials. (October 2018) - Pemberton, Victoria L; Evans, Frank; Gulin, Jamie; Rosenberg, Ellen; Addou, Ebyan; Burns, Kristin M; Gordon, David J; Pearson, Gail D; Kaltman, Jonathan R
Background/Aims: Identifying predictors of recruitment success in clinical trials, particularly prior to study launch, could contribute to higher study completion rates and improved scientific return on investment. This article evaluates the performance of clinical trials funded by the National Heart, Lung, and Blood Institute that began recruitment before and after implementation of National Heart, Lung, and Blood Institute's 2009 Accrual Policy and identifies study-related factors that predict recruitment success. Methods: A retrospective analysis of National Heart, Lung, and Blood Institute's cardiovascular clinical trials with initial funding from 1996 to 2012 was performed to assess recruitment success. Success was defined as ≥100% enrollment of the proposed sample size within the duration initially proposed by investigators. Trials were assigned to categories (pre-policy vs post-policy) based on whether the first patient was enrolled before or after the 2009 Accrual Policy implementation. Potential determinants of successful recruitment were evaluated using multivariable logistic regression. Results: Of 167 trials analyzed, 26.3% met the definition of success. Twenty-four trials (14.4%) were terminated early and 15 (62.5%) for insufficient recruitment. Trials failed due to <100% enrollment (22.8%), longer duration (19.8%), or both (31.1%). Trials testing behavioral interventions, those conducted within a National Heart, Lung, and Blood Institute–funded network, and those with normal controls were predictive of success. The proportion of successful clinical trials increased from 23% in the pre-policy era to 30% post-policy, although the difference was not statistically significant ( p  = 0.29). Conclusion: Enrollment success rates for National Heart, Lung, and Blood Institute's clinical trials are concerning. The 2009 National Heart, Lung, and Blood Institute Accrual Policy did not significantly improve trial success. Clinical trials testing behavioral interventions, those conducted within networks, and those with normal controls were predictive of recruitment success. Components of networks may provide model practices to help other trials attain success, including close attention to oversight activities such as recruitment plans, real-time enrollment monitoring, corrective action plans to address shortfalls, and close sponsor-investigator collaborations.